PENGARUH KUALITAS PELAYANAN, KAPABILITAS INOVASI, DAN CITRA PERUSAHAAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Indomaret di Daerah Sukun, Kota Malang) - Donny Pangestu; Rois Arifin; M.Hufron M.Hufron (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT The purpose of this study was to determine the effect of service quality, innovation capabilities and corporate image on consumer loyalty through satisfaction as an intervening variable.The population of this study consisted of 605 consumers of breadfruit indomaret. The sample used was 82 samples that met the criteria in the research subject. The analytical method used is the normality test, path analysis test, t test and sobel test.The results showed that there was an effect of Service Quality, Innovation Capability, and Company Image on Customer Loyalty through Customer Satisfaction at Indomaret Sukun. Keywords: Service Quality, Innovation Capability, Corporate Image, Customer Loyalty and Customer Satisfaction